Wheat Pill Poisoning: Clinical Manifestation and its Outcome - Alina Hassan ,Muhammad Shehzad Manzoor ,Muhammad Shafique ,Adil (Journal of Rawalpindi Medical College, 2014)
Background: To determine the clinical features and outcome in patients presenting with wheat pill poisoning. Methods: In this descriptive study 77 patients with wheat pill ingestion were included. The diagnosis was based on basis of history of consumption of wheat pills. All patients were given initial resuscitation e.g. gastric lavage with vegetable oil and shifted to intensive care unit. Serial ECG and arterial blood gases were done. If pH was less than 7.2, alkali therapy in the form of NaHCO3 (Usually 7.5% Solution) was initiated. Amiodarone was given for arrhythmias and infusion inotrops (i.e. dopamine & dobutamine) to correct hypotension. End point was death or shifting back to respective medical unit. Result: Out of 77 patients, majority (53%) were females. Maximum patients belonged to age group (20 – 30 yrs) i.e. 45 patients. Severe Metabolic acidosis was the commonest cause of death. Overall mortality was 33%. Common symptoms were vomiting, hypotension, arrhythmias, irritability, confusion and metabolic acidosis. Patients who consumed more than on tablet did not survive Patient who presented late, i.e., after 12 hrs, succumbed to death. Conclusion: Wheat pill is very common mode of suicide in a country like Pakistan as it is freely available and cheap. Arrhythmia and metabolic acidosis is the major cause of death after wheat pills ingestion.